COVID-19 SCHOOL CLOSURES IMPACTS ON PRIMARY SCHOOL STUDENTS MATHEMATICS COMPETENCE - Mardyanto Barumbun; Soma Salim S (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
School closures and home learning policy to prevent the spread of COVID-19 in Indonesia raised concerns about learning loss. This research was focused on examining the potential for learning loss in terms of the mathematical competence of year-3 indigenous primary school students in Indonesia due to school closures during the pandemic. This qualitative research with a phenomenological approach involved 8 year-3 students who had been studying from home for the last 1.5 years or so. Data collection was carried out using mathematical diagnostic tests and interviews. Results from this study revealed the phenomenon of learning loss in terms of the mathematical competence among the students, where the mastery of prior mathematics knowledge and skills required for grade 3 were not mastered yet. Also, their mathematical competences were below the competency standard in the curriculum for grade 3 primary school in Indonesia. The significancy of this study emphasized that the phenomenon of learning loss that occurred in primary school students during and even after the COVID-19 pandemic should be a serious concern for all parties and stakeholders. Hence, some solutions and quick steps that need to be taken to mitigate the long-term impacts of learning loss are also included in this article.